Addressing the Needs of Women and Girls in Contexts of Forced Displacement : Experiences from Operations - Hanmer, Lucia; Arango, Diana; Damboeck, Johanna; Rubiano, Eliana; Villacres, Daniela (World Bank, Washington, DC, 2019)
This review focuses on women and girls who have been forcibly displaced. Gender inequality is not left behind when women and girls are forced to flee their homes. In situations of displacement, women and girls are most exposed to adversity, and many of the risks they face, such as gender-based violence, are heightened. Women are among the most vulnerable, facing a number of challenges including extreme poverty, lack of access to basic infrastructure and services, and the impacts of climate change on livelihoods and human well-being. Internalized inequality can limit women's ability to overcome adverse experiences. With that in mind, World Bank projects must consider the different circumstances of women and girls/men and boys to deliver benefits to those that need them most. The objective of this portfolio review is twofold: (i) to assess how World Bank operations to date have addressed the different needs of forcibly displaced women and girls/men and boys in fragile, conflict, and violence (FCV) contexts; and (ii) to distill lessons and guidance for task teams, including those designing operations under the new International Development Association (IDA18) refugee window and the Global Concessional Financing Facility (GCFF). The review is limited to considering how the needs of women and girls have been addressed, as no operations were found that identified gender specific needs of forcibly displaced men and boys, or sought to close gender gaps that affected these men and boys adversely.